First polymorphisms in JY-1 gene in cattle (Bos taurus indicus) and their association with sexual precocity and growth traits - Ferreira de Camargo, Gregorio Miguel [UNESP]; Cardoso, Diercles Francisco [UNESP]; Monsalves Gil, Fernanda Maria [UNESP]; Silva Fonseca, Patricia Dias da [UNESP]; Zetouni, Larissa [UNESP]; Braz, Camila Urbano [UNESP]; Freitas, Ana Claudia de [UNESP]; Pablos de Souza, Fabio Ricardo [UNESP]; Aspilcueta-Borquis, Rusbel Raul [UNESP]; Baldi, Fernando [UNESP]; Albuquerque, Lucia Galvão de [UNESP]; Almeida Regitano, Luciana Correia de; et al. (Springer, 2012)
Protein JY-1 is a bovine oocyte-specific protein that regulates granulosa cell function and is involved in early embryonic development, influencing the chance of pregnancy. This study investigated molecular markers for the JY-1 gene. Seven SNPs were identified in exon 3 of the gene. The positions of the SNPs in the exon and the respective substitutions are: 163 (T/C), 281 (T/C), 321 (T/C), 532 (T/C), 652 (A/G), 679 (T/C), and 722 (G/C) (GenBank: JN592587 and JF262042.2). SNP 163 is located in a coding region and causes a proline-to-leucine substitution. The other SNPs are located in the 3'UTR region. SNPs 163, 281, 321, and 679 were genotyped in 297 Nellore heifers and the haplotypes were constructed. The haplotypes of JY-1 were not correlated with the traits studied at 5 %.
Keywords: Molecular markers; Nellore; SNP; reproductive traits; Chromosome 29